SPORTS PERFORMANCE AS A MODERATOR OF THE RELATIONSHIP BETWEEN COPING STRATEGY AND EMOTIONAL INTELLIGENCE (Kinesiology, 2020)
The sample consisted of 171 elite and 169 non-elite athletes. linear regression analysis was used to test the prognostic role of emotional competence on stress coping strategies, and hierarchical regression analysis was used to test the moderating role of performance in the relationship between emotional competence and coping strategies. The result shows that EI is related to task-oriented strategies and completely unrelated to emotion-oriented strategies. Sport performance moderates the relationship between managing and regulating emotions and using avoidant coping strategies, in a way that non-elite athletes with higher scores on this EI subfactor are more likely to use distraction-oriented coping.Key words: emotional intelligence, coping, moderation, elite and non-elite athletes